2010
DOI: 10.1097/bpb.0b013e32833ccac2
|View full text |Cite
|
Sign up to set email alerts
|

Congenital postero-medial bowing of the tibia and fibula: is early surgery worthwhile?

Abstract: We report the results of surgical treatment of congenital postero-medial bowing of the tibia and fibula. Twenty patients with congenital postero-medial bowing were seen with nine patients treated surgically (corrective osteotomy or lengthening and deformity correction with Ilizarov fixator) and 11 patients managed conservatively. The angles of medial and posterior angulation and limb length discrepancy were recorded serially and compared. Surgical complications were recorded. The mean follow-up was 9.5 and 6.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 8 publications
5
22
0
Order By: Relevance
“…It is accepted that remodelling is not usually complete, and that leg-length discrepancy (LLD) increases with age and may be up to 7 cm at maturity. 4 , 5 , 7 Some authors have suggested that surgery should play a greater role in the management of posteromedial bowing than simple epiphysiodesis, either through the use of osteotomy for deformity correction 7 - 9 and/or limb lengthening techniques. 7 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…It is accepted that remodelling is not usually complete, and that leg-length discrepancy (LLD) increases with age and may be up to 7 cm at maturity. 4 , 5 , 7 Some authors have suggested that surgery should play a greater role in the management of posteromedial bowing than simple epiphysiodesis, either through the use of osteotomy for deformity correction 7 - 9 and/or limb lengthening techniques. 7 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…In the second patient, six weeks after complition of lengthening, LCP was inserted and Ilizarov frame was subsequently removed during the same operation (Figure 4). Residual LLD after tibial lengthening in CPMBT has been observed by many authors (2,5,6,12). The first of our patients on the last follow-up visit, five years after lengthening, had no LLD but 0.5 cm of overcorrection have been lost.…”
Section: Figure 2 Progression Of Lld With Growth (Case 4) On Ap X-rmentioning
confidence: 77%
“…Shah et al (6) reported about two patients treated with lengthening. Johari et al (12) performed six lengthening procedures for an average preoperative LLD of 3.93 cm. Finally, Kaufman (2) has recently published the results of treatment of 11 patients whose mean LLD was 3.7 cm.…”
Section: Figure 2 Progression Of Lld With Growth (Case 4) On Ap X-rmentioning
confidence: 99%
“…In this century, only two papers have been published that have described surgical treatment of patients with the congenital posteromedial bowing of the tibia and fibula [5,6]. Shah et al [5] described a total of nine patients who were operated on.…”
Section: Discussionmentioning
confidence: 99%
“…Johari et al [6] described nine cases -three were singlelevel osteotomies, another three were single-level osteotomies with lengthening and the other three were multilevel osteotomies with axis correction at one level and lengthening at the second level. The authors determined the tibia and fibula bowing exceeding 301 as a recommendation to osteotomy.…”
Section: Discussionmentioning
confidence: 99%